CHANGES IN HOMEOSTASIS INDICATORS OF ORAL FLUID IN CHILDREN AT THE STAGES OF ORTHODONTIC TREATMENT - Tuychiyev Rashidbek Valijon og’li (Scholars Digest Publishing, 2024)
This study investigates the alterations in homeostasis indicators of oral fluid during different stages of orthodontic treatment in children. The research employs a longitudinal approach, tracking changes in salivary pH, electrolyte levels, and enzymatic activity before treatment initiation, during active treatment, and post-treatment. Special emphasis is placed on understanding how orthodontic appliances and interventions influence these biomarkers, which are critical for oral health maintenance. Insights gained from this investigation contribute to optimizing orthodontic protocols and improving patient outcomes by addressing potential disruptions in oral fluid homeostasis throughout the course of treatment.
Keywords: orthodontic treatment, oral fluid, homeostasis indicators, salivary pH, electrolytes, enzymatic activity, children, dental health, treatment stages.